In situ and in vitro determination of the protein value of feeds for ruminants. Issue 5 (3rd September 2021) - Rupp, Christiane; Westreicher-Kristen, Edwin; Susenbeth, Andreas
ABSTRACT: The objective of this study was to estimate the amount of post-rumen crude protein (prCP), a precursor to metabolisable protein for ruminants, of feeds and feed mixtures using an in situ and in vitro method, and to contrast the results of both approaches. For this, 34 samples were examined: 9 feeds, 13 feed mixtures made thereof and 12 feed mixtures provided by commercial dairy farms. As a minor aspect, additivity of protein values from feeds was evaluated by comparing measured and calculated values of feed mixtures. Effective prCP was calculated for assumed rumen passage rates ( k ) of 0.05 h −1 (prCP5 ) and 0.08 h −1 (prCP8 ) by in situ measurements of rumen undegraded CP and fermented organic matter (FOM) assuming an efficiency of 181 g microbial CP/kg FOM. Additionally, effective prCP in vitro was estimated using the modified Hohenheim gas test (modHGT) through incubation in rumen-fluid buffer solution for 8 and 24 h followed by ammonia distillation. In vitro estimations were highly correlated with in situ values for both passage rates ( k = 0.05 h −1 : p < 0.001, R 2  = 0.68; k = 0.08 h −1 : p < 0.001, R 2  = 0.76). The in vitro method yielded higher values for effective prCP than the in situ approach with 29 g/kg OM ( k = 0.05 h −1 ) and 37 g/kg OM ( k = 0.08 h −1 ) on average for all samples. Small positive associative effects – reflecting non-additivity – were found, averaging at 2.2 g prCP8 /kg OM ( p < 0.05) for the in situ and 10.7 g prCP8 /kg OM ( p < 0.001) for the in vitro approach. Due to the need of an assumption of a certain value for microbial efficiency in situ, effective prCP might be more accurately estimated in vitro, accounting for nutrient-specific efficiencies as well as interactions between carbohydrate and protein degradation by rumen microbes. Furthermore, the modHGT highlighted associative effects more pronounced and seems suitable as a routine method due to the comparably low effort and high sample throughput. The potential of the modHGT to determine the protein value of feeds could be demonstrated by our study.